Strict versus negligence software product liability - Abdullah, Farhah; Jusoff, Kamaruzaman; Mohamed, Hasiah; Setia, Roszainora (2009)
The law of products liability in tort is designed to maintain a reasonable balance between the inevitable social costs and the benefits of innovative product technologies. Technological development must be supported not only for the best interests of the public but also the side effect namely product defect into one of the following: (1) manufacturing defect; failures to correctly implement safety measures from the design; and (2) design defects: failures of the design itself to exhibit socially acceptable levels of safety. Software has been described as an artifact with fundamentally different properties than other engineered artifacts. This article will discuss several issues such as identifying the features of high technology products which lead to difficulties in applying traditional tort notions to them.